Fabry disease in unselected patients with TIA or stroke: Population-based study - Marquardt, L; Marquardt, L; Baker, R; Segal, H; Burgess, A; Poole, D; Hughes, D; Rothwell, P (2012)
Background: Fabry disease (FD) is an X-linked lysosomal storage disorder frequently associated with cerebrovascular disease. In recent years, the prevalence of FD has been reported to be up to 4% in cryptogenic young stroke patients. However, there have been no population-based studies in unselected patients with transient ischaemic attack (TIA) or stroke across the full range of ages. Methods: We determined the prevalence of FD mutations in consecutive patients from a population-based study of acute TIA or ischaemic stroke (Oxford Vascular Study). Analysis included amplifying of the α-galactosidase A gene by polymerase chain reaction, denaturing high-performance liquid chromatography (dHPLC) analysis and sequencing using standard automated sequencing protocols [Mutation Surveyor software (Softgenetics)] where the dHPLC indicated a possible mutation. Results: Samples of 1046 consecutive patients (52% women; mean age 73.2 years; 15% age <60 years; 572 stroke; 474 TIA) were tested. No patient had a known gene mutation causing FD, giving an upper 95% confidence interval around the estimated frequency of 0.35% overall and 2.37% in the 154 patients aged under 60 years. However, in 5 (0.48%) samples, a known polymorphism or sequence variation in the gene was identified that can be associated with lower than normal enzyme activity in plasma without causing the full clinical manifestation of FD. Conclusions: Fabry disease is rare in an unselected group of UK patients with TIA or stroke. Larger studies in unselected younger patients with cryptogenic stroke are required to determine whether routine screening is justified in this group. © 2012 EFNS.